2013
DOI: 10.1111/1567-1364.12075
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-induced apoptosis of yeast cells is associated with mitochondrial superoxide radical accumulation and NAD(P)H oxidation

Abstract: In previous studies, we observed that aspirin, a promising cancer-preventive agent, induces apoptosis in mitochondrial manganese superoxide dismutase (MnSOD)-deficient Saccharomyces cerevisiae cells grown aerobically in ethanol medium. In this study, we show that aspirin-induced apoptosis is associated with a significant increase in mitochondrial and cytosolic O2 ·- and oxidation of mitochondrial NAD(P)H. A concomitant rise in the level of cytosolic CuZnSOD activity failed to compensate for mitochondrial MnSOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…Slightly elevated adduct rates in WBC were determined in few welders using acetylsalicylic acid as medication. The latter observation is in line with in vitro studies where acetylsalicylic acid induced apoptosis by increasing the production of ROS (Farrugia et al 2013 ; Raza et al 2011 ).…”
Section: Discussionsupporting
confidence: 84%
“…Slightly elevated adduct rates in WBC were determined in few welders using acetylsalicylic acid as medication. The latter observation is in line with in vitro studies where acetylsalicylic acid induced apoptosis by increasing the production of ROS (Farrugia et al 2013 ; Raza et al 2011 ).…”
Section: Discussionsupporting
confidence: 84%
“…and oxidation of mitochondrial nicotinamide adenine dinucleotide phosphate hydrogen. 8 However, the mechanism underlying the effect of aspirin is still unclear.…”
mentioning
confidence: 99%
“…cerevisiae cells, but not in wild-type yeast cells, during aerobic growth in ethanol medium 1821 . We also showed that the aspirin-induced apoptosis in redox-compromised MnSOD-deficient yeast cells is associated with severe mitochondrial dysfunction, including events such as overproduction of mitochondrial superoxide radicals (O 2 ˙ − ), oxidation of mitochondrial NAD(P)H 21 , decreased respiration, release of cytochrome c and disruption of the mitochondrial membrane potential 20 . Overall, these results indicated that the mitochondrial milieu constitutes a critical cellular target of aspirin.…”
Section: Introductionmentioning
confidence: 92%